A Generation at Risk: The Impacts of Lebanon's Escalating Humanitarian Crisis on Children - Abouzeid, Marian; Halwani, Dana A.; Mokdad, Ali H.; Habib, Rima R. (Frontiers in Public Health, 2021)
Lebanon is in the midst of a rapidly escalating, unprecedented humanitarian crisis that is plunging the country deep into poverty and threatens population wellbeing, economic development, social welfare and national and regional stability. The dire situation is due to the compounding effects of the August 2020 Beirut blast, massive economic collapse and the COVID-19 pandemic, in a setting of longstanding entrenched political corruption and a dysfunctional, mismanaged crisis response by the state. This current emergency occurs on the background of a turbulent history and complex regional geopolitical context – including the Syrian refugee crisis, the ongoing influence of foreign actors and their local proxies, the United-States-imposed sanctions, endemic corruption, a culture of nepotism and entitlement among the political dynasties, dysfunctional power-sharing and deep-seated sectarian divides. With over half the population now living in poverty, a generation of children are among those at risk. This Perspective provides a brief overview of Lebanon’s current complex humanitarian crisis, discusses the impacts of the evolving situation on youth and proposes a suite of recommendations to mitigate the effects.